Improving the Health of Older Prisoners: Nutrition and Exercise in Correctional Institutions. (October 2018) - Wangmo, Tenzin; Handtke, Violet; Bretschneider, Wiebke; Elger, Bernice S.
This qualitative article presents and compares the views of older prisoners and expert stakeholders on the topic of nutrition and exercise. The study highlights measures for improving the health of older prisoners. Older prisoners report the need to improve quality of meals provided in prison. They note that prison food is of poor quality and not adapted to their needs. With regard to exercise, they point out the lack of proper opportunities to engage in exercise and sports, and describe several factors that make physical activities either unsuitable or unfeasible. Expert stakeholders see prison as an opportunity to improve the health of those convicted of crimes. In light of the increasing number of older prisoners, age-appropriate nutritional and exercise interventions should take priority in prisons.